PROCESSING OF EXHAUST LEADEN-CADMIUM GALVANICELEMENTS REPORT 1. PRINCIPLES AND PROCESSES OF PROCESSING - Дмитриков, В. П.; Падалка, В. В.; Проценко, О. В.; Коломєєц, В. І. (Scientific Progress & Innovations, 2013)
The results of researches are resulted on the reagent processing of exhaust leaden-cadmium galvanic elements and accumulators which serve as the second raw material for electrical engineering industry. The method of processing is developed zero-emission, energy- and resourses economy, ecologically safe, at the same time remaining maintenance of lead, does not exceed cadmium and their connections ecological standards. Chemical and technic processes are analysed, the offered is improved methodology and the general chart of technology of processing of leaden-cadmium galvanic elements and accumulators is developed.